Dermaseptin-Based Antiviral Peptides to Prevent COVID-19 through In Silico Molecular Docking Studies against SARS-CoV-2 Spike Protein - Fakih, Taufik Muhammad (Pharmaceutical Sciences and Research, 2020)
A pandemic coronavirus disease of 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has now been declared a global pandemic by the World Health Organization. The search for new drugs, especially by utilizing antiviral peptides is a very potential area. Through this study, protein-peptide docking and protein-protein docking simulations were conducted using in silico methods to identify, evaluate, and explore the molecular affinity and interaction of dermaseptin peptide molecules produced by frogs of the genus Phyllomedusa against the SARS-CoV-2 spike protein macromolecule, and its effect on attachment to the surface of the ACE-2 (Angiotensin Converting Enzyme-2) receptor. Protein-peptide docking simulation results show that dermaseptin-S9 peptide molecule has the best affinity to the active site of SARS- CoV-2 spike protein macromolecule binding site, with a binding free energy value of −792.93 kJ/mol. Then the results of protein-protein docking simulations proved that dermaseptin-S9 peptide molecule was able to prevent the attachment of SARS-CoV-2 spike protein to the surface of the ACE-2 receptor, with a total energy value of 517.85 kJ/mol. Therefore, it is hoped that dermaseptin-S9 peptide molecule can be further studied in the development of novel antiviral peptide candidates for the control of COVID-19 infectious disease.